Purification and characterization of a bacterial phytase whose properties make it exceptionally useful as a feed supplement - Greiner, Ralf; Farouk, Abd Elaziem Aziem (Springer, 2007)
A periplasmatic phytase from a bacterium isolated from Malaysian waste water was purified about 173-fold to apparent homogeneity with a recovery of 10% referred to the phytase activity in the crude extract. It behaved as a monomeric protein with a molecular mass of about 42 kDa. The purified enzyme exhibited a single pH optimum at 4.5. Optimum temperature for the degradation of phytate was 65C. The kinetic parameters for the hydrolysis of sodium phytate were determined to be KM = 0.15 mmol/l and kcat = 1164 s)1 at pH 4.5 and 37C. The purified enzyme was shown to be highly specific. Among the phosphorylated compounds tested, phytate was the only one which was significantly hydrolysed. Some properties such as considerable activity below pH 3.0, thermal stability and resistance to pepsin make the enzyme attractive for an application as a feed supplement.